Germany’s stance on the Nord Stream 2 project: Internal and external determinants - F. А. Basov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In recent years, Germany’s energy policy has been pursuing several long-term goals: not only to ensure energy security, but also to achieve energy transition and to become a major gas hub in the European Union. In that context, cooperation with Russia as a key exporter of natural gas to Germany was of particular importance. At the same time, relations between the two states showed contradictory dynamics. This became especially evident during the political struggle over the project of the new Nord Stream 2 gas pipeline. The author traces the evolution of the arguments of the key participants in the discussions sparked by the project in Germany before Russia began its special military operation in Ukraine and after it. The first section examines the positions of the main interest groups, leading political parties and regional authorities. The author shows that representatives from the business community and political forces related to them (SPD, CSU, part of the CDU and FDP) were generally inclined to support the project, albeit under certain conditions. The latter particularly included Russia’s guarantees for preserving gas transit through Ukraine. The human rights (legalist) group and eco-activists, affiliated with the Greens, partly the CDU and the FDP, took a much more critical stand regarding Nord Stream 2. Moreover, the federal government’s policy was greatly affected by a number of external factors. Germany made significant diplomatic efforts not only to coordinate its position with other EU countries, but also to overcome the resistance to the project from the United States and Ukraine. Nevertheless, the German government eventually managed through various compromises to advance the Nord Stream 2 project. The situation has changed dramatically after Russia’s recognition of the Donetsk People’s Republic and Luhansk People’s Republic. The German government halted the process of certification of Nord Stream 2. All major German political parties supported this decision.